The constitutional development of fundamental rights and the horizontal application of the Bill of Rights under the South African constitution of 1996 - von Samson-Himmelstjerna, Armin (Centre for Law and Society, 2024)
Human rights undoubtedly playing an important role in the modem world and they are now recognised in most parts of the world. Many states incorporated these rights into their constitution under the heading of 'Bill of Rights'. Several different definitions, of the term 'human rights' exist but none of them is generally accepted. Intuitively, the word 'human' suggests that this right applies to every human being. The question of whether the term 'human' also covers the unborn child or a dead person, too, is also a controversial question and is not fully discussed. Presently it can be said, that the term 'human' at least covers every human being from birth until dead. The issue of what kind of rights human rights are is also a very controversial one. However, for the purpose of this discussion, human rights shall be understood as the basis of all rights which people have and ... human rights are those liberties, immunities and benefits which, by accepted contemporary values, all human beings should be able to 'as of right' of the society in which they live. This thesis will deal with the development of the application of human rights in states' constitutional systems. As with historical development it will deal with human rights as rights of the individual against the state. Then the application of the Bill of Rights in the private sector will be closely examined in regard to the South African Interim- and Final Constitution.